New infrared spectra of CO2–Xe: modelling Xe isotope effects, intermolecular bend and stretch, and symmetry breaking of the CO2 bend. (3rd June 2021) - Barclay, A. J.; McKellar, A. R. W.; Western, Colin M.; Moazzen-Ahmadi, N.
Abstract : The infrared spectrum of the weakly bound CO2 –Xe complex is studied in the region of the carbon dioxide ν3 fundamental vibration (≈2350 cm −1 ), using a tunable OPO laser source to probe a pulsed supersonic slit jet expansion. The Xe isotope dependence of the spectrum is modelled by scaling the vibrational and rotational parameters, with the help of previous microwave data. The scaling model provides a good simulation of the observed broadening and (partial) splitting of transitions in the fundamental band, and it is essential for understanding the intermolecular bending combination band where some transitions are completely split by isotope effects. The combination band is influenced by a significant bend–stretch Coriolis interaction and by the relatively large Xe isotope dependence of the intermolecular stretch frequency. The weak CO2 –Xe spectrum corresponding to the (01 1 1) ← (01 1 0) hot band of CO2 is also detected and analysed, providing a measurement of the symmetry breaking of the CO2 bending mode induced by the nearby Xe atom. This in-plane/out-of-plane splitting is determined to be 2.14 cm −1 . GRAPHICAL ABSTRACT: UF0001